RUSSIA IN CENTRAL ASIA: RETREAT, RETENTION,OR RETURN? - TOLIPOV, Farkhod (CENTRAL ASIA AND THE CAUCASUS, 2007)
On 18 October 2004, the Russian Federation joined the Central Asian Cooperation Organization (CACO) and so can be called a Central Asian state. This distorted the region’s geography and changed its political composition. On 13 December 1991, five Central Asian states (Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan) set up this integration structure in response to the Soviet Union’s breakup and the creation of the Commonwealth of Independent States (CIS), which was, at first, purely Slavic. The events of 1991 are directly related to the present and provide answers to many of the questions raised by the transformations going on in the newly independent states (NIS) and their foreign policy. It is often—and correctly—said that the former Soviet republics were not ready for independence; in fact, it seems that Russia itself was not ready for it. Yet it was Russia that sent the ball of breakup rolling in June 1991: it declared independence and challenged the results of the all-Union referendum that took place earlier, on 17 March and formalized the will of the people to preserve the Union. Russia’s political step was absolutely senseless: all the republics that united around it in the 1920s completely depended on it. In this context, Russia’s present attempts at “gathering in the lands” it itself scattered look paradoxical. To succeed it must revise two major issues: (1) the principles of the 1991 disintegration and (2) the principles of 21st century reintegration. Stephen Cohen, professor of Russian history at New York University, has correctly pointed out that those who want to understand Putin’s Russia would do best to put it in the context of a national collapse that followed the Soviet Union’s breakup. He says: “It is hard to imagine a political act more extreme than abolishing what was still, for all its crises, a nuclear superpower state of 286 million citizens. And yet Yeltsin did it, as even his sympathisers acknowledged, in a way that was ‘neither legitimate nor democratic.’ ...Political and economic alternatives still existed in Russia after 1991, and none of the factors contributing to the end of the Soviet Union were inexorable.”1 This goes contrary to the more or less commonly accepted opinion (mainly in Russia and the Soviet successor states) that the Soviet Union was doomed because its political system was in a deep crisis. The West never expected, and did not want, this tragedy. Much was done to help President Mikhail Gorbachev to keep his country afloat.2 Today, Russia, when dealing with the former Soviet republics, works hard to pretend that the year 1991 can be dismissed as an ordinary event to be rectified through reunification. The laws of history and international relations (which we, the political scientists, discover and study) will not allow Russia to succeed in its integration contrivance (so far this is a contrivance and nothing more), which will remain half-backed and will look suspicious and even provocative. All integration processes develop along certain patterns and are based on certain principles and values. This much has already been proven by the theoreticians of integration. This means that to remain within strictly academic limits, we should investigate the sources, driving forces, principles, aims, effects and even the moral fundamentals of the policies the CIS countries are pursuing in their mutual relations. This primarily applies to Russia’s policy toward its CIS colleagues. We would do best to start from the very beginning and look back at the events of 1991. The type of relations still prevailing among the NIS was imposed by Russia on the eve of the Soviet Union’s breakup. I am inclined to call it Yeltsin’s heritage. It destroyed or pushed away the type of relations born by the perestroika (a period that is almost forgotten), which I prefer to describe as Gorbachev’s approach.